Sustainable resort construction: A tool for economic development? The cases of Rosalie Bay Resort, Dominica and MT. Plaisir Estate, Trinidad. - Sachs, Daniella (My University, 2012)
Tourism has been identified by “developing world” governments and multilateral lending agencies as an important driver for economic development. Current research is focused on improving tourism operations’ (pro-poor) economic linkages with the local community. The aim of this study is to evaluate the extent to which the construction phase of sustainable resort development can contribute to these strategies, in rural coastal areas. This qualitative study is conducted by means of a comprehensive literature review and multi-case study evaluation. The construction phase of Rosalie Bay Resort, Dominica, and Mt. Plaisir Estate Hotel, Trinidad, are evaluated according to a ‘value chain’ analysis of economic linkages, leakages, and their accompanying socio-economic impacts. The findings demonstrated that the construction process makes a valuable contribution to tourism-led economic development, through the provision of temporary and sustained employment opportunities; alternative livelihoods; increased earning capacity; diversified income sources; improved employability; and heightened self-esteem.